ANALISIS LITERASI KIMIA PESERTA DIDIK KELAS XI IPA PADA MATERI STOIKIOMETRI DI SMA NEGERI 12 KENDARI - Alfina. M, Nurafipah; Fahyuddin, Fahyuddin; Musta, Rustam (FKIP UM Pontianak, 2026)
Chemical literacy is an essential competency that supports students’ understanding of chemical concepts and their application in real-life contexts. However, numerous studies indicate that the level of scientific literacy among Indonesian students, including chemical literacy, remains relatively low. Stoichiometry is one of the chemistry topics that requires a high level of chemical literacy due to its abstract nature and its reliance on quantitative reasoning. This study aimed to analyze the level of chemical literacy of Grade XI science students on stoichiometry at SMA Negeri 12 Kendari. This study employed a quantitative approach with a descriptive research design. The research population consisted of 103 Grade XI science students, from which 51 students were selected as the sample using a simple random sampling technique. The research instrument was a 25-item two-tier diagnostic multiple-choice test designed to measure chemical literacy aspects, including knowledge, application, and nature of science. Data were analyzed using descriptive statistical techniques, including mean scores, standard deviation, and percentage analysis. The results showed that students’ chemical literacy levels were predominantly in the moderate category, with a mean score of 61.45. The percentage of students in the low, moderate, and high categories was 29.4%, 39.2%, and 31.4%, respectively. These findings indicate that students have acquired basic understanding of stoichiometric concepts but still encounter difficulties in applying these concepts to more complex contexts. Therefore, it is recommended that innovative and contextual learning models be implemented to enhance students’ chemical literacy.